ORIENTASI PASAR DAN BUDAYA ORGANISASI DALAM MEMPENGARUHI INOVASI DAN KINERJA PEMASARAN - Viajeng Purnama Putri; Ratya Shafira Arifiani (Magister Manajemen STIE Bank BPD Jateng, 2022)
Appropriate market orientation and a strong organizational culture are required to improve marketing performance by allowing product innovations to be created in accordance with business needs, which have an impact on marketing performance. This research was conducted on Small and Medium Enterprises (SMEs) in Malang City, where SMEs have an important role in the economy in Indonesia. The focus of this research is to see if market orientation has an impact on innovation, organizational culture has an impact on innovation, innovation has an impact on marketing performance, and the role of innovation in mediating market orientation on marketing performance and organizational culture on marketing performance. The main objective of this study is on the owner of a small firm in Malang City, as measured by market orientation, organizational culture, innovation, and marketing performance. Explanatory research is used in this work, which takes a quantitative method. The findings show that market orientation influences innovation, that organizational culture influences innovation, that marketing performance is influenced by market orientation, organizational culture, and innovation, and that marketing performance is mediated by market orientation and organizational culture..